2012
DOI: 10.1158/1078-0432.ccr-12-1257
|View full text |Cite
|
Sign up to set email alerts
|

Src Inhibition with Saracatinib Reverses Fulvestrant Resistance in ER-Positive Ovarian Cancer Models In Vitro and In Vivo

Abstract: Purpose More effective, less toxic treatments for recurrent ovarian cancer (OVCA) are needed. Although >60% of OVCAs express the estrogen receptor (ER), ER-targeted drugs have been disappointing due to drug resistance. In other estrogen-sensitive cancers, estrogen activates Src to phosphorylate p27 promoting its degradation and increasing cell cycle progression. Since Src is activated in most OVCAs, we investigated whether combined Src and ER blockade by saracatinib and fulvestrant would circumvent antiestroge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 53 publications
2
90
0
Order By: Relevance
“…28 Recently, it was shown that ERα blockade effectively arrested breast cancer cells at G 1 cell cycle by stabilizing p27. 30,31 However, the roles of ERβ1 and ERβ2 in this process have not yet been clearly established.…”
Section: Lapatinib Induces P27mentioning
confidence: 99%
“…28 Recently, it was shown that ERα blockade effectively arrested breast cancer cells at G 1 cell cycle by stabilizing p27. 30,31 However, the roles of ERβ1 and ERβ2 in this process have not yet been clearly established.…”
Section: Lapatinib Induces P27mentioning
confidence: 99%
“…Endocrine therapy using aromatase inhibitors to block estrogen production, or tamoxifen and other competitor antiestrogens, often results in selection and outgrowth of resistant tumors. Although 30-70% of epithelial ovarian tumors are ERα-positive (1), endocrine therapy is largely ineffective (5)(6)(7). After several cycles of chemotherapy, tumors recur as resistant ovarian cancer (5), and most patients die within 5 years (8).…”
mentioning
confidence: 99%
“…Increased pSrc was also observed in cell line M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT models of fulvestrant resistance (83,84). In two studies, researchers noted that with increased number of passages, PEO1 and Skov3 ovarian cancer cells developed de novo resistance to growth inhibition by treatment with fulvestrant (83,84). Dual treatment with fulvestrant and saracatinib, a Src inhibitor, overcame this resistance in vitro and in vivo; the combination led to increased autophagy and apoptosis.…”
Section: Development Of Resistance To Serdsmentioning
confidence: 82%
“…Models of fulvestrant resistance have also been developed in ovarian cancer.Fulvestrant resistance that has recently emerged is via activation of c-Src, a non-receptor tyrosine kinase (83,84). Elevated pSrc in ER positive ovarian tumors correlated with poor worse clinical outcome after estrogen antagonist treatment (84).…”
Section: Development Of Resistance To Serdsmentioning
confidence: 99%
See 1 more Smart Citation